Communication Management via WhatsApp in Hajj and Umrah Travel Agencies: A Qualitative Study in Indonesia - Taqqiya, Khalwa Rofida; Airlangga Bramayudha (PROGRESIF: Jurnal Dakwah, Sosial, dan Komunikasi, 2025)
This study explores the role of WhatsApp as a communication management tool in Hajj and Umrah travel agencies. The background of this research lies in the increasing reliance on digital communication platforms for religious tourism services, where effective communication is essential for ensuring smooth operations and building pilgrims’ trust. The objective of this study is to analyze how WhatsApp supports administrative processes, religious guidance, emergency handling, and marketing, while also identifying challenges faced in its implementation. Using a qualitative approach with interviews, observations, and documentation, the study provides comprehensive insights into communication practices. Results show that WhatsApp significantly enhances efficiency in disseminating information, strengthens relationships between agencies and pilgrims, and contributes to pilgrims’ satisfaction. However, issues such as information overload, the digital divide among elderly pilgrims, and privacy concerns remain challenges that require structured management. The study concludes that WhatsApp is not merely a messaging platform but a strategic communication tool that aligns with Media Richness Theory, Uses and Gratifications Theory, and Islamic business ethics. This research contributes to communication science by contextualizing digital media use in religious tourism and provides practical implications for improving service quality in Hajj and Umrah travel management.